Optimization of Pre-Inoculum, Fermentation Process Parameters and Precursor Supplementation Conditions to Enhance Apigenin Production by a Recombinant Streptomyces albus Strain - Simona Barbuto Ferraiuolo; Odile Francesca Restaino; Ignacio Gutiérrez-del-Río; Riccardo Ventriglia; Marcella Cammarota; Claudio J. Villar; Felipe Lombó; Chiara Schiraldi (Fermentation, 2021)
Streptomyces albus J1074-pAPI (Streptomyces albus-pAPI) is a recombinant strain constructed to biotechnologically produce apigenin, a flavonoid with interesting bioactive features that up to now has been manufactured by extraction from plants with long and not environmentally friendly procedures. So far, in literature, only a maximum apigenin concentration of 80.0 µg·L−1 has been obtained in shake flasks. In this paper, three integrated fermentation strategies were exploited to enhance the apigenin production by Streptomyces albus J1074-pAPI, combining specific approaches for pre-inoculum conditions, optimization of fermentation process parameters and supplementation of precursors. Using a pre-inoculum of mycelium, the apigenin concentration increased of 1.8-fold in shake flask physiological studies. In 2L batch fermentation, the aeration and stirring conditions were optimized and integrated with the new inoculum approach and the apigenin production reached 184.8 ± 4.0 µg·L−1, with a productivity of 2.6 ± 0.1 μg·L−1·h−1. The supplementation of 1.5 mM L-tyrosine in batch fermentations allowed to obtain an apigenin production of 343.3 ± 3.0 µg·L−1 in only 48 h, with an increased productivity of 7.1 ± 0.1 μg·L−1·h−1. This work demonstrates that the optimization of fermentation process conditions is a crucial requirement to increase the apigenin concentration and productivity by up to 4.3- and 10.7-fold.